2017
DOI: 10.21276/ap.2017.6.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Effect of demographic location on Phlebodiumdecumanum (Willd.) J. Sm. for its phytoconstituents and establishment of antioxidant and novel anthelmintic activity of its aqueous and methanolic leaf extracts

Abstract: A fern, Phlebodium decumanum (Willd.) J.Sm. (PD) belongs to the family Polypodiaceae. It is a creeping, densely hairy or scaly rhizome bearing fronds at intervals along its length. It is native to tropical and subtropical regions of the America. The present study was investigated to establish the presence of phytoconstituents in leaf samples collected from three different geographical zones (Bengaluru, Nasik, and Munnar) and their impact on antioxidant and anthelmintic activity. Aqueous and methanol leaf extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Further, it is also revealed that percentage yield of extract also higher in methanol extract than others (Arawwawala and Wickramaarachchi, 2012;Akowuah et al, 2014) and the same trend followed in the present study where methanol extract of callus showed higher percentage of yield than aqueous extract. It is also proved that content of active constituents are also depends on the percentage of yield (Dent et al, 2013;Das et al, 2016;Das et al, 2017). Our present study is also reported the similar results that influence direct correlation with the amount content of the active constituents.…”
Section: Hplc Methodssupporting
confidence: 88%
“…Further, it is also revealed that percentage yield of extract also higher in methanol extract than others (Arawwawala and Wickramaarachchi, 2012;Akowuah et al, 2014) and the same trend followed in the present study where methanol extract of callus showed higher percentage of yield than aqueous extract. It is also proved that content of active constituents are also depends on the percentage of yield (Dent et al, 2013;Das et al, 2016;Das et al, 2017). Our present study is also reported the similar results that influence direct correlation with the amount content of the active constituents.…”
Section: Hplc Methodssupporting
confidence: 88%
“…Hence, plants containing useful phytochemicals may supplement the of the human body by acting as natural antioxidants. These phytoconstituents depend on the geographical location where the plant material collected [ 29 ] and the season as well as the maturity of leaves [ 30 ]. The chemical profile and antioxidant activities of V. amygdalina grown in the study area is not reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…But the main concern is to discovery of new drugs from the plant extracts which is more potent than the extracts against any kind of human health hazards. The main reason behind the selection of these two plants leaf because both the plants enhanced the immunity and act strongly against any infections due to their high antioxidant activities 36,10 . It was revealed that selected plant extracts showed significant antipsoriasis activity due to the presence of important secondary metabolites (discussed earlier in introduction part).…”
Section: Antipsoriasis Activitymentioning
confidence: 99%
“…Scientifically leaves are also claimed as having antimicrobial activity 7 , hepatoprotective activity 8 and wound healing activity 9 . Thereafter Phlebodium decumanum (PD) (family Polypodiaceae), commonly known as ornamental fern, is abundantly available in damp region of many places in India 10 . The leaves contains many chemicals viz.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation